2021
DOI: 10.3389/fpsyt.2021.710878
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Mental Health Disorder and Substance Abuse of Chinese International College Students During the COVID-19 Pandemic

Abstract: Introduction: The outbreak of coronavirus disease has negatively impacted college students' mental health across the world. In addition, substance abuse also is trouble among these students. This study aims to find the gender difference in Chinese international college students' mental health and substance abuse during the COVID-19 pandemic.Method: We conducted an online survey using PHQ-9, GAD-7, and several questions related to substance abuse frequency, self-injury, and suicidal thoughts, 535 male and 475 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…As such, the gender difference in BA observed in our sample is consistent with results from previous college student studies (10,66,67) as well as a meta-analysis of 40 studies indicating university women generally report less BA than university men do (14). Also in line with general psychiatry references and China-based epidemiological studies on gender differences in psychiatric symptoms, women in our sample reported significantly higher severities of depressive symptoms, anxiety symptoms and fatigue (65,(68)(69)(70)(71), hypothesized to result from gender differences in various biological and psychosocial factors (72)(73)(74). Notably, however, the gender difference in BA found in this study could not be explained by corresponding links between gender and these psychiatric disturbances or specific demographics that were statistically controlled in associated analysis.…”
Section: Gender Differences In Body Appreciationsupporting
confidence: 91%
“…As such, the gender difference in BA observed in our sample is consistent with results from previous college student studies (10,66,67) as well as a meta-analysis of 40 studies indicating university women generally report less BA than university men do (14). Also in line with general psychiatry references and China-based epidemiological studies on gender differences in psychiatric symptoms, women in our sample reported significantly higher severities of depressive symptoms, anxiety symptoms and fatigue (65,(68)(69)(70)(71), hypothesized to result from gender differences in various biological and psychosocial factors (72)(73)(74). Notably, however, the gender difference in BA found in this study could not be explained by corresponding links between gender and these psychiatric disturbances or specific demographics that were statistically controlled in associated analysis.…”
Section: Gender Differences In Body Appreciationsupporting
confidence: 91%
“…The outbreak of health emergencies resulting from coronavirus disease 2019 (COVID- 19) not only negatively impacted the mental and physical health of the general population but also increased the incidence of psychological crises (1,2). A growing literature revealed that many individuals were experiencing severe psychological burden during this period across countries (3)(4)(5)(6); stressors involve social isolation, health concerns, fears of being infected, and stigma, which resulted in a series of negative emotional problems, fear, anxiety, and frustration.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that Chinese international students have experienced these negatively biased and perceived discriminations and anxiety during the period ( 15 17 ). A profound long-term negative influence, such as depression and anxiety levels, has changed Chinese college students' experiences in America ( 5 ). Against this background, we want to find the difference between CSC and CSA by analyzing the prevalence of mood disorders and substance use problems to provide evidence for the prevention and clinical treatment of mental health problems of the college students' population.…”
Section: Introductionmentioning
confidence: 99%
“…With or without a pandemic, people may generally seek relief from mental health distress by engaging in pleasurable activities such as alcohol and other drug use [11][12][13][14][15] and sex 16,17 . Pre-COVID, social isolation and migration-related distress have been linked with risky sexual practices and poor sexual health outcomes among international students in Australia 18, 19 .…”
Section: Introductionmentioning
confidence: 99%
“…While a large body of evidence indicates increased alcohol and other drug use among young people because of the psychological distress associated with the COVID-19 pandemic, especially during and after the restrictive lockdowns [20][21][22][23][24] , evidence around the use of sex to mitigate the psychological impact of the pandemic is scarce. Most of what we know about sex during COVID-19 lockdowns is largely based on solitary sexual practices [25][26][27] , which may not answer the critical question around how the pandemic may be shaping BBV/STI risk practices among young people.…”
Section: Introductionmentioning
confidence: 99%